Pengaruh Modal Sosial dan Dukungan Kelembagaan Terhadap Tingkat Keberdayaan Petani Kakao di Wilayah Sekitar Pertambangan Kabupaten Bulungan - Suryatno, Iwan; Setiawan, Iwan; Yudha, Eka Purna (Universitas Galuh, 2025)
Empowered farmers have the capacity to make choices, access resources, and increase income which in turn can improve their livelihoods. Therefore, the level of empowerment of farmers is crucial to ensure the sustainability of their businesses and to overcome challenges such as unpredictable agricultural conditions. In addition to the importance of farmers' empowerment level, it is also necessary to pay attention to factors that can support the creation of farmers' empowerment in running their business. This study aims to analyze the influence of social capital and institutional support on the level of empowerment of cocoa farmers in the area around mining in Bulungan Regency, especially farmers assisted by PT Pesona Khatulistiwa Nusantara (PKN). The approach used in this research is descriptive quantitative with a case study method. Respondents were determined based on the census method of 108 cocoa farmers assisted by PT PKN. Data were analyzed using descriptive analysis techniques and multiple linear regression. The results showed that there is a simultaneous influence of social capital, and institutional support on the level of farmer empowerment. Partial test results of social capital has a significant influence on the level of farmer empowerment (0.037), with an average value indicating that farmers have a fairly good social network consisting of institutional networks, trust, cooperation and norms. However, institutional support did not show a significant effect on the level of farmer empowerment (0.267), which is due to the mismatch of policies with farmers' needs, lack of coordination between institutions, and limited assistance resources. These findings indicate the importance of strengthening social capital and improving institutional support to strengthen farmer empowerment. Some concrete efforts suggested to improve farmer empowerment include adjusting policies to farmers' needs and strengthening cocoa farmers' social networks.